360‐degree video offloading using millimeter‐wave communication for cyberphysical system. Issue 4 (16th August 2018) - Kim, Hyun‐Wook; Le, Tuan Thanh; Ryu, Eun‐Seok
Abstract: This paper describes an adaptive scheme of 360‐degree video streaming over millimeter‐wave (mmWave) communication for cyberphysical system. It consists of two parts, ie, (1) 360‐degree video streaming and offloading over mmWave 802.11ad 60 GHz wireless link and (2) 360‐degree video decoding, postprocessing, and display by using scalable high‐efficiency video coding. The mmWave communication is high‐speed wireless technology to increase the capacity of video transmission. However, current studies on video streaming over mmWave focus on long distance, and mobile devices process many tasks such as video decoding, postprocessing, and display by themselves. Therefore, the performance of mobile device seriously degrades in the case of high‐resolution video streaming, such as 4K. Furthermore, the synchronization of real‐time video streaming at high speed is an important issue to ensure the quality of service (QoS), especially when the mobile device is moving. Thus, this paper focuses on real‐time video streaming over mmWave with optimized QoS for high‐resolution video. Furthermore, this study implemented an offloading mechanism to handle the offloading tasks between a powerful GPU‐based PC and a mobile device. The experimental results show that the proposed method provides high‐performance 360‐degree video streaming in QoS‐sensitive video streaming applications. Abstract : 360 video offloading over mmWave communication for cyberphysical system.